THE PSYCHOLOGICAL IMPACT OF ALEX STANDALL ON THE DEATH OF HANNAH BAKER ON NETFLIX'S THIRTEEN REASONS WHY (2017) - Ayuningtyas Putri Pratiwi; Yeny Prastiwi (Dialectical Literature and Educational Journal, 2020)
This study aims to determine the psychological impact experienced by Alex Standall on the death of Hannah Baker, presented in the Thirteen Reasons Why series adaptation of the novel of the same title by Jay Asher. This study is a qualitative research. The data source used is the TV-series Thirteen Reasons Why first season. The data collection technique is from analyzing the series. The theory used in this study is the psychology of literature. The results of this study are as follows: first, the initial factors that triggered Alex Standall to do bad things to Hannah Baker. Second, the psychological condition of Alex Standall after making a mistake about Hannah Baker. Third, the guilty towards Hannah Baker that caused Alex Standall finally decided to end his life.